Judicial authority, dissent and the project of international justice - Mistry, Hemi (2016)
Dissenting opinions, separate opinions and declarations are a familiar aspect of the international jurisprudential landscape. Despite this, in comparison to domestic judicial systems, there has been comparatively little by way of attempts to rationalise the institutional and systemic implications of this practice. While there is widespread agreement that the impact of additional opinions lies in their effect upon the authority of the court or tribunal and its decisions (‘institutional judicial authority’), the nature of that impact is open to greater contestation. How should additional opinions be viewed? An unnecessary and counterproductive distraction or an important mechanism of accountability for the exercise of judicial power?